Fixed prosthesis on teeth and implants: a case report (Research, Society and Development, 2021)
Several factors can cause tooth loss in the individual, impairing facial harmony and the physiology of the stomatognathic system, influencing mainly on chewing, phonation and joint balance. In more complex cases involving multiple tooth losses, it is necessary to reestablish the vertical dimension of occlusion (VDO), as well as the search for aesthetics and increased self-esteem are constantly required. The objective of this work will be to report a clinical case of oral rehabilitation with implant supported prosthesis associated with dental supported prosthesis, in which the VDO, aesthetics, function and balance of the stomatognathic system will be restored. The treatment of the 56 years old, leucoderma, male patient, was carried out at the dental clinic of the University Center of Volta Redonda and after anamnesis, clinical examination, analysis of the photographs, panoramic radiography and the study models, it was observed loss of masticatory function, aesthetics and collapse in the vertical dimension of occlusion. The patient denied allergies and reported being diabetic and hypertensive, but under treatment to control these morbidities. Oral rehabilitation was performed through the confection of a modified Branemark protocol fixed prosthesis over teeth and implants. It is concluded that patient satisfaction was evident with the improvement of functional and aesthetic by the installation of the provisional prosthesis modified protocol from PMMA acrylic resin, satisfactorily answering all the necessary requirements until this rehabilitation phase, restoring the vertical dimension of occlusion, returning masticatory efficiency, as well as rebalancing the stomatognathic system psychosocially influencing his quality of life.